Therapeutic modulation of the natural history of coronary atherosclerosis: lessons learned from serial imaging studies - Andrews, Jordan (Cardiovasc Diagn Ther, 2016)
Despite advances in risk prediction, preventive and therapeutic strategies, atherosclerotic cardiovascular disease remains a major public health challenge worldwide, carrying considerable morbidity, mortality and health economic burden. There continues to be a need to better understand the natural history of this disease to guide the development of more effective treatment, integral to which is the rapidly evolving field of coronary artery imaging. Various imaging modalities have been refined to enable detailed visualization of the pathological substrate of atherosclerosis, providing accurate and reproducible measures of coronary plaque burden and composition, including the presence of high-risk characteristics. The serial application of such techniques, including coronary computed tomography angiography (CTA), intravascular ultrasound (IVUS) and optical coherence tomography (OCT) have uncovered important insights into the progression of coronary plaque over time in patients with stable and unstable coronary artery disease (CAD), and its responsiveness to therapeutic interventions. Here we review the use of different imaging modalities for the surveillance of coronary atherosclerosis and the lessons they have provided about the modulation of CAD by both traditional and experimental therapies.